Corporate social responsibility (csr) for education in Malaysia: a systematic literature review. - Senin, Muhammad Adam; Halim, Harliana; Ramdzan Ali, Al Amirul Eimer (Hampstead Psychological Associates, 2019)
Corporate Social Responsibility (CSR) is one of the ways for any private organisation or individual to contribute to the society as a form of giving back to the community. The services offered may vary according to the capability of the institutions involved. This include financial assistance, school supplies, expertise, skills and knowledge sharing and social work. Besides that, the idea of contributing and donating to the society is an ideal way to ease the burden of the government and local authorities. Particularly, in education sector CSR has become a great way for the organisations to expand their contribution in schools and society. There are many benefits and advantages of having the CSR programmes especially in the education development. This literature review writing explored the involvement of the organisations and individuals in helping the Malaysia education system via CSR initiatives. Scholars research findings and analysis through documents such as newspaper report are essential in promoting the CSR programmes in the country. The benefits and advantages towards the school, teachers, pupils and the local community were explained to create awareness among the society about the importance of giving back in the education sector.